Blood Pressure Thresholds for Hypertension in Pregnancy and Future Cardiovascular Risk - Kattah, Andrea G; Coutinho, Thais D; Vermunt, Jane; Vaughan, Lisa E; Suvakov, Sonja; Butler Tobah, Yvonne S; Chamberlain, Alanna M; Bielinski, Sue J; Garovic, Vesna (Mayo Clinic proceedings, 2025)
To evaluate the impact of blood pressure threshold (≥140/90 vs ≥130/80 mm Hg) and cardiovascular disease (CVD) risk factors on the association of hypertensive disorders of pregnancy (HDP) and CVD. A cohort of parous women 45 years of age were followed up for an average of 18.6 years. Hypertension in pregnancy was defined using 2 thresholds: ≥140/90 and ≥130/80 mm Hg (with more than 50% of readings greater than or equal to threshold after first elevation). Cox proportional hazards models were used to evaluate the association between HDP and CVD after adjusting for CVD risk factors (at age 45 or as time-dependent covariates after 45), age at first pregnancy, and parity. Among 1755 women, 263 (15.0%) had HDP during one or more of their pregnancies using the 140/90 mm Hg or greater threshold, while 780 (44.4%) had HDP based on the 130/80 mm Hg or greater threshold. Adjusting for age at pregnancy, parity, body mass index, and CVD risk factors after age 45, both term and preterm preeclampsia were associated with an increased risk of CVD using the 140/90 mm Hg or greater threshold (hazard ratio (HR), 1.45; 95% CI, 1.00 to 2.09; P=.048; and HR, 2.25; 95% CI, 1.25 to 4.06; P=.007, respectively) and the 130/80 mm Hg or greater threshold (HR, 1.42; 95% CI, 1.01 to 1.99; P=.042; and HR, 1.98; 95% CI, 1.09 to 3.60; P=.024, respectively). Women who had HDP only at 130/80 mm Hg or greater (not ≥140/90 mm Hg) had a lower prevalence of hypertension at 45 years compared with the higher threshold (11.0% [57 of 517] vs 24.7% [63 of 263]; P<.001). Lowering the blood pressure threshold increased the incidence of HDP but did not impact the association of HDP and future CVD.